Antimalaria Medicine and Its Mechanism : A Review - Nor Latifah; Anas Subarnas; Anis Yohana Chaerunisaa (Universitas Padjadjaran, 2020)
Malaria is a deadly disease caused by Plasmodium infection that is spread by female Anopheles. Malaria is a serious and deadly disease due to Plasmodium infection which is spread by female Anopheles mosquitoes. Among the five Plasmodium species, the most common species attacking humans are the Plasmodium falciparum and Plasmodium vivax species. Decreased sensitivity resulting in continuous and inadequate treatment, causing parasitic mutations, other than that allegedly originating from resistant areas. The purpose of this paper is to find out some anti-malaria drugs and the mechanism of action used in Indonesia based on references from the current development of anti-malaria drugs. While the benefits are providing information about antimalarial drugs and the mechanism of action in the use of drugs in Indonesia for malaria. Treatment of malaria is classified into 3, namely: classification of malaria drugs based on the workings of drugs in the Plasmodium life cycle, classification of antimalarial drugs based on the chemical structure of the drug, and classification of antimalarial drugs based on the workplace of the drug in the Plasmodium subcellular organelle.Keywords: Malaria, Plasmodium, antimalarial, mechanism